Development of Control System for TU-2A CNC Machine - Ariawan Bayu Wicaksono; Lewi; Muh. Abdillah; Nurhidayanti; Ishak (METAL: Jurnal Sistem Mekanik dan Termal, 2026)
This study aims to design and develop an electronic control system for the TU-2A CNC machine to improve its performance, simplify the programming process, and facilitate machine maintenance and repair procedures. The method used is retrofitting the EMCO TU-2A CNC machine by replacing the old electronic components with more modern and affordable components, without compromising the machine's precision. Calibration is carried out to ensure the accuracy of the machine's movement, while machine testing is conducted by machining workpieces made of teflon (PTFE) and aluminum. The results of the study indicate that after the development and maintenance, the CNC TU-2A machine showed improvements in precision and ease of use. The machine's error remains within the tolerance limit, approximately 0.01 to 0.02 mm, indicating that the calibration was successful. The conclusion of this study is that the development of the new electronic control system has made the CNC TU-2A machine more efficient and easier to maintain, making it more suitable for use in vocational education.